The comparison of the impact of ghrelin and tacrolimus on vitreous cytokine levels in an experimental uveitis model - Gul, Fatih Cem; Turgut, Burak; Dagli, Ferda; Ilhan, Nevin; Ozgen, Metin (Springer, 2013)
We aimed to compare the effects of intraperitoneal ghrelin and tacrolimus on vitreous levels of tumor necrosis factor-alpha (TNF-alpha), interleukin-1 (IL-1), and interleukin-6 (IL-6) in an experimental autoimmune uveitis model. Twenty-four male rats, each weighing 300 g, were assigned into four groups, six rats in each. All the rats, except for those in group 1, were injected intravitreally with concanavalin a to induce experimental uveitis. The development of uveitis was confirmed by the histopathologic examination of two rat globes from each group. The rats in group 2 were not given any treatment after uveitis was induced. The rats in group 3 were administered 1 mg/kg/day of intraperitoneal tacrolimus on days 0, 1, 3, 5 and 7 following the induction of uveitis (on the 14th day of study). The rats in group 4 were given 10 ng/kg/day of intraperitoneal ghrelin for 7 days following the induction of uveitis. On the 21st day of the study, all rats were sacrificed, and the eyes enucleated were subjected to histopathologic examination. Vitreous levels of TNF-alpha, IL-1 and IL-6 were measured by the enzyme-linked immunosorbent assay method. The histopathologic evaluation carried out to confirm the development of uveitis revealed destruction in the retinae and ciliary bodies of the immunized rats. The mean vitreous levels of TNF-alpha, IL-1 and IL-6 were significantly higher in the sham group than in the control group (p < 0.05). The levels of these three cytokines showed a significant decrease in the tacrolimus treatment group (p < 0.05). Cytokine levels decreased in the ghrelin treatment group relative to the control group; however, the decrease was not found statistically significant (p > 0.05). Tacrolimus could be effective in uveitis treatment by neutralizing or decreasing the levels of cytokines such as TNF-alpha, IL-1 and IL-6 that have a critical part in the pathogenesis of uveitis. However, ghrelin failed to produce the desired effect. Further studies using different doses and different ways of administration are needed to determine the effective dose of ghrelin in uveitis.
Keywords: Uveitis; TNF-alpha; IL-1; IL-6; Tacrolimus; Ghrelin